2017
DOI: 10.1177/0271678x17741395
|View full text |Cite
|
Sign up to set email alerts
|

Imaging microglial activation and amyloid burden in amnestic mild cognitive impairment

Abstract: Amnestic mild cognitive impairment (aMCI) is defined as a transitional state between normal aging and Alzheimer's disease (AD). Given the replicated finding of increased microglial activation in AD, we sought to investigate whether microglial activation is also elevated in aMCI and whether it is related to amyloid beta (Aβ) burden in-vivo . Eleven aMCI participants and 14 healthy volunteers completed positron emission tomography (PET) scans with [F]-FEPPA and [C]-PIB. Given the known sensitivity in affinity of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 45 publications
1
22
0
Order By: Relevance
“…Overall, tau, amyloid, and TSPO radiotracers show good ability in the detection of AD and MCI, in addition to associated neuropathology (Table 5) Hamelin et al, 2016;Knezevic et al, 2017;Parbo et al, 2017;Parbo et al, 2018). Whilst older and using smaller samples, studies indicating negative or no association between microglial activation and Aβ accumulation (Kreisl et al, 2013;Wiley et al, 2009;Yokokura et al, 2011) highlights the need for future research to clarify the nature of this relationship using in vivo brain imaging technology.…”
Section: Interplays Between Tau Amyloid and Microgliamentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, tau, amyloid, and TSPO radiotracers show good ability in the detection of AD and MCI, in addition to associated neuropathology (Table 5) Hamelin et al, 2016;Knezevic et al, 2017;Parbo et al, 2017;Parbo et al, 2018). Whilst older and using smaller samples, studies indicating negative or no association between microglial activation and Aβ accumulation (Kreisl et al, 2013;Wiley et al, 2009;Yokokura et al, 2011) highlights the need for future research to clarify the nature of this relationship using in vivo brain imaging technology.…”
Section: Interplays Between Tau Amyloid and Microgliamentioning
confidence: 99%
“…Similar to [ 11 C]PK11195, in vivo increases in TSPO binding are associated with impairments in global cognition and memory (Hamelin et al, 2018;Kreisl et al, 2013), but also extend to domains that include visuospatial and language ability, and executive functioning, in addition to dementia severity and brain atrophy (Hamelin et al, 2018;Kreisl et al, 2013;Kreisl et al, 2016;Suridjan et al, 2015). However, some studies demonstrate no such correlations with the ADAS-Cog or MMSE (Yasuno et al, 2008;Yasuno et al, 2012) upregulated cortical tracer retention when compared to healthy controls, especially in the temporal lobe Yasuno et al, 2012), and others showing no such significant differences (Knezevic et al, 2017;Kreisl et al, 2013).…”
Section: Second-generation Tspo Tracersmentioning
confidence: 99%
“…PET investigation of AD patients indicated only a low correlation between cerebral amyloid burden and cognitive performance (15), and Ab deposition precedes the onset of neuroinflammation in patients with mild cognitive impairment (16). We contend that the temporal sequences of Ab deposition and microglial activation in relation to progression of cognitive impairment is best examined through molecular imaging studies of longitudinal design.…”
mentioning
confidence: 96%
“…Fewer studies have examined the association of TSPO binding particularly with EM performance. One study found that worse delayed word list recall score was associated with higher TSPO binding in the precuneus in Alzheimer’s disease ( Passamonti et al , 2018 ), while two studies did not find a correlation with delayed verbal EM test scores ( Kreisl et al , 2017 ; Knezevic et al , 2018 ).…”
Section: Discussionmentioning
confidence: 99%